AutoFeed: Smart IoT Fish Feeding - Rosdin, Mohamad Faiz; Abdul Jalil, Rozita (Applied Information Technology And Computer Science, 2026)
The AutoFeed: Smart IoT Fish Feeding aims to help the fish owner take care of their fish by automating the feeding process, reducing the manual method, and ensuring proper nutrition. Many fish owners face difficulties in maintaining regular feeding schedules, which can lead to overfeeding or underfeeding the fish, causing harm. This project automates the feeding process using IoT integration, reducing the need for pet owner intervention while ensuring the fish receive the correct amount of food at the right time. The system integrates an ESP32 Microcontroller, Ultrasonic Sensor, and LCD I2C 16x2, along with a mobile application built using Flutter and connected to Firebase to store data, control the feeder, set feeding schedules, monitor food level, and receive low food level alerts. The system successfully automated the feeding process and future work could include smart home integration and AI-based adaptive scheduling.